Redesigning Blended Learning Models in The Era of Artificial Intelligence - Mustakul, Setiyawan; Syarovina, Malfika (Generate Digital Publishing, 2024)
Objective: The objective of this study is to explore the role of Artificial Intelligence (AI) as a transformative technology in education, particularly in the context of blended learning. The study aims to assess the impact of AI tools on learning personalization, assessment automation, and student-teacher interaction, while addressing ethical and operational challenges. Research Design & Methods: This study utilizes a library research method, analyzing various AI tools and their application in education, including smart tutoring systems such as Google Classroom, ChatGPT, Turnitin, and Gradescope. Findings: The findings suggest that AI tools significantly enhance learning outcomes and student engagement by personalizing learning experiences and automating assessments. However, challenges such as over-reliance on AI, privacy risks, and ethical concerns need to be addressed for the successful integration of AI in education. Implications & Recommendations: The study recommends that AI integration in education should be done in a balanced way, through collaboration between governments, educational institutions, and technology providers, and supported by clear regulations to reduce risks. Educators also need to combine AI with effective pedagogical practices to support the development of critical thinking and problem-solving skills in students. Contribution & Value Added: This research contributes to the understanding of how AI can enhance blended learning by offering a comprehensive analysis of its tools and their impact on education. It also provides practical recommendations for educators and policymakers to optimize the use of AI, while addressing its challenges in the digital age.